Information-structural perspectives on discourse particles - Modicom, Pierre-Yves; Duplâtre, Olivier (Studies in language companion series,, 2020)
"The articles collected in this volume offer new perspectives into the relevance of notions such as topic, antitopic, contrastive topic, focus, verum focus and theticity for the analysis of the syntax and semantics of modal particles, sentence-final particles and other medial, sentential and illocutive particles. This book addresses three great questions in a variety of languages ranging from Japanese to Mohawk, including Basque, French, German, Italian, Kazakh, Spanish and Turkish, with some insights from English and Russian. The first question is the role played by information-structural strategies such as left dislocations, clefts or the morphological marking of focus in the rise of discourse particles. In the second part, papers are concerned with the relevance of information structure for the study of polysemic and polyfunctional discourse particles. Finally, the contribution of particles to the determination of the information-structural profile of the clause is examined, as well as their role in the information-structural specification of illocutionary types. Language-specific papers alternate with comparative approaches in order to show how newer insights on information structure can help resolve some of the classical issues of the linguistic research on particles"--